PENGARUH KEPUTUSAN INVESTASI DAN GOOD CORPORATE GOVERNANCE PADA KINERJA KEUANGAN SERTA IMPLIKASINYA PADA NILAI PERUSAHAAN - Dewi, Lini Novita; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2015)
This research was conducted in order to know the influence investment decisions and good corporate governance which is proxied by managerial ownership on financial performance and its implications on firm value. The sample in this study 66 manufacturing companies that meet the criteria for purposive sampling. The data analysis technique used in this study path analysis. The results of the analysis concluded that affect investment decisions on firm value different from managerial ownership has no effect on firm value, whereas investment decisions and managerial ownership indirect effect on firm value through financial performance .
Keywords: investment decisions, managerial ownership, financial performance, firm value